Development of Magnetic Capture Hybridization and Quantitative Polymerase Chain Reaction for Hepatitis B Virus Covalently Closed Circular DNA - Guo, Yongcan (Hepat Mon, 2015)
BACKGROUND: Hepatitis B virus (HBV) covalently closed circular DNA (cccDNA) served as a vital role in the life cycle of the virus and persistent infection. However, specific and quantitative methods for cccDNA detection have not been available. OBJECTIVES: Our aim was to develop and primarily evaluate a quantitative method for HBV cccDNA based on magnetic capture hybridization and quantitative PCR technology. MATERIALS AND METHODS: The functionalized-nanoparticles specifically to capture HBV cccDNA, located on both sides of relaxed circle DNA (rcDNA) gap, were designed. Then, magnetic capture hybridization and quantitative PCR (MCH-qPCR) assay were developed and its performance was primarily evaluated with cccDNA standards and serum samples of patients with chronic hepatitis B. RESULTS: Specific nanoparticles of cccDNA capture were prepared and a magnetic capture hybridization and quantitative assay method for cccDNA was developed successfully. The limit of detection was 90 IU/mL, and a good linear relationship in the range of 10(2)-10(6) IU/mL was revealed (r(2) = 0.994) with the MCH-qPCR. Compared with directly real-time PCR, a high content of HBV DNA did not affect the detection of cccDNA for the MCH-qPCR method, and there was no cross-reactivity between cccDNA and rcDNA. CONCLUSIONS: The novel MCH-qPCR method has good sensitivity and specificity. It could meet the requirement of clinical routine detection.